Utilisation of Self-Hypnosis Techniques as an Effective Method in Increasing an Athlete's Concentration - Nurhayati, Maya; Sahudi, Udi; Yudha, Brio Alfatihah Rama; Septiani, Nala (Journal of Physical Education Health and Sport, 2023)
This study aims to investigate the use of self-hypnosis techniques as an effective method of increasing the concentration of athletes. In the world of competitive sports, high concentration is a key factor to achieve optimal performance. However, many athletes face challenges in maintaining their focus during training and competition. The self-hypnosis method has been identified as a potential tool for increasing mental concentration. This study involved 12 athletes in the petanque sport and used an experimental research design. Participants are trained in self-hypnosis techniques and then given practise sessions involving situations that require high concentration. The results showed that the use of self-hypnosis significantly increased the concentration levels of athletes during training and competition. In addition, the positive effects of self-hypnosis can last a longer period of time. These findings provide evidence that self-hypnosis can be a valuable tool in helping athletes achieve optimal performance through increased mental concentration. The practical implication of this study is that sport trainers and developers may consider using self-hypnosis techniques as part of a training programme to effectively increase athlete concentration.